(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Studies on local body temperatures improve the potential for analysis of biological processes in organs and tissues of the body. A study on changes in ocular surface temperature in an animal model of non-infectious uveitis for objectively assessing ocular inflammation is planned for the future. Purpose: To determine normal temperatures of the ocular surface in the projection of the ciliary body in rabbits. Material and Methods: Temperature of the ocular surface in the projection of the pars plana was measured in 42 Chinchilla rabbits using a thermoelectric device. Results: There was no significant difference in mean temperature between the nasal ocular surface and the temporal ocular surface in the projection of the ciliary body (34.13 °С (SD=1.45) against 34.09 °С (SD=1.48), p = 0.57). In addition, there was a very weak correlation of room temperature with body temperature and ocular surface temperature. Mean ocular surface temperature for the right eye was 34.1°С (SD=1.43), and for the left eye, 34.2°С (SD=1.43), but the difference in this measure between the right and left eyes was not significant (р = 0.27). Conclusion: There was no significant difference in the temperature of the ocular surface in the projection of the ciliary body between the right and left eyes in the absence of pathological changes. The mean temperature of the ocular surface in the projection of the ciliary body in intact rabbits was 34.1°С (SD=1.4). Temperature of the ocular surface in the projection of the ciliary body in rabbits is characterized by autonomic thermoregulation and is relatively stable at small environmental temperature variations. The pattern of heat exchange in rabbit’s ocular surface allows for modeling of unilateral ocular pathological processes that would have a change in local body temperature in the projection of the ciliary body as an objective marker.